Image retrieval of motifs in malay vernacular architecture / Puteri Nor Hashimah M. A. Rahman, Mohd Sabrizaa Abd. Rashid and Baharum Baharudin - M. A. Rahman, Puteri Nor Hashimah; Abd. Rashid, Mohd Sabrizaa; Baharudin, Baharum (2012)
In this paper, we propose a simple yet effective technique of indexing and retrieval of motifs from the carvings found in the Malay vernacular architecture. The algorithm will further classify the motifs into two main codes, i.e, Bunga' code and 'Daun' code. The 'Bunga' code will be sub-categorized into eight types and the 'Daun' code will also be sub-categorized into eight types. Hence, given an input motif image, it is expected that it will output the correct motif classification. The proposed algorithm will not only retrieve the motifs automatically but it will also create a database of digitized motifs.